BONGGOL KAYU SEBAGAI MEDIA EKSPRESI KRIYA LOGAM - Khairunas Khairunas (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
jungle is heritage for offspring as well as God blessing that we always take care, because it existence is very important for life in the world. Jungle must be kept and be continuous. Indeed, we realize that jungle or trees is water reservoir and air neutralizer, but actually most of jungle is cut without good planning. In today contexts, disaster such as flood, landslide and poor air are back grounded by jungle destruction and its ecosystem. The making of this work through three steps namely exploration such as idea resource exploration, design, and realization thruogh looking for creative and innovative new form based opn modrn sclupture rule. Work realization use wood lump media, copper alloy using mosaic technique, cast and welding. In its realization, it emphasize on expression without leaving meaning and implicit message in creation idea resource. Work creation is not only related to visual beauty, but also related to meaning and work content. Work with three dimension form is visualization from illegal logging and its by product such as wood lump. The meaning from real form in art that created is expression of feeling and observation process on phenmena that happen in Indonesian jungle. This creation is hope to be able to one of effort to attract people symphathy and make mistake in value of jungle and plant existence so that they cannot continuous further namely jungle exploitation out of normality